ANALISIS PEMANFAATAN MEDIA SOSIAL OLEH HUMAS KOTA SOLOK DALAM MEWUJUDKAN “KOTA BERAS SERAMBI MADINAH” MENGGUNAKAN MEDIA RICHNESS THEORY - Dhiki Hamdhany; Emeraldy Chatra; Sarmiati Sarmiati (Ensiklopedia of Journal, 2021)
Solok City Public Relations utilizes social media in carrying out its duties to support government work programs. The city of Solok has the slogan "Kota Beras Serambi Madinah" which reflects the vision and mission of the city of Solok in the context of the work program of the Mayor and Deputy Mayor. This study was conducted to analyze the use of social media by Public Relations of Solok City in realizing “Kota Beras Serambi Madinah” using Media Richness Theory by Richard L. Daft and Robert H. Lengel. This study uses a qualitative method, constructivist paradigm with a case study approach. Informants were determined by purposive sampling technique, conducted in-depth interviews, observation, documentation, data analysis and data validation. The results of the study found that Solok City Public Relations tried to use all the wealth of social media to realize the goals that have been set. One type of social media has two different accounts (profiles) with different language variations and signs to reach more audiences, anticipate the rapid exchange of information on social media and promote the Solok City Public Relations website. The ability of social media to show feelings and emotions is used by the Public Relations of Solok City to instill the values contained in the slogan " Kota Beras Serambi Madinah"